PERAN BEA DAN CUKAI DALAM PELAYANAN DAN PENGAWASAN FASILITAS KAWASAN BERIKAT UNTUK PENINGKATAN INVESTASI DI KOTAMADYA MEDAN - Franky Damanik; Robert; Ningrum Natasya Sirait (Smart Education, 2026)
Medan City Customs and Excise Supervision and Services (KPPBC) in the implementation of Bonded Zone facilities as an instrument for increasing investment and strengthening the competitiveness of national industry. The problem in this study focuses on how the implementation of services and supervision of Bonded Zone facilities by KPPBC Medan City and various legal and administrative challenges faced in supporting increased investment. Although Bonded Zone facilities provide various fiscal incentives and procedural conveniences that are proven to be able to increase exports and attract investment, there are still obstacles in the form of complexity of supervision, lack of synchronization of legal regulations, lack of norms related to inspection and assistance mechanisms, limited supervisory resources, and potential injustice for industries outside the Bonded Zone. The research method used is normative legal research with an approach to legal principles, legal systematics, legal synchronization, and laws and regulations related to Bonded Zones. The results of the study indicate that KPPBC Medan City has carried out its service and supervision role quite effectively through the provision of fiscal facilities, simplification of electronic-based customs procedures, fast licensing services, technical assistance to business actors, and risk management-based supervision. This policy has had a positive impact on company operational efficiency, increased exports, and investment growth in Medan City. However, various challenges remain, including regulatory inconsistencies, legal gaps in certain oversight mechanisms, limited resources, and the need for a more balanced oversight model that balances facilitation and law enforcement functions. Therefore, strengthening regulatory harmonization, improving the quality of assistance, optimizing inter-agency coordination, and developing risk-based oversight are necessary to create legal certainty and a more conducive investment climate.